Aspectual class (under-)specification in the generation of motion event representations: a project outline : working paper - Gerwien, Johannes; Herweg, Michael (Heidelberg University papers on language & cognition, 2017)
In this working paper, we outline a research program that focuses on Aspectual Class interpretation in descriptions of motion events. First, we briefly sketch the research program and motivate our endeavour by reviewing current formal semantic and psycholinguistic research in the field. We place special focus on the theoretical concept of lexical semantic underspecication. Second, we define the goals that we will pursue in this project and highlight our theoretical starting points, both from the viewpoint of formal semantics and psycholinguistics. Third, we give an outlook for the next steps to be taken.